Everyday music - Govenar, Alan B. (John and Robin Dickson series in Texas music, 2012)
During the 1980's and again from 2009-2011, folklorist Alan Govenar traveled all over the state of Texas to interview local performers of traditional music of all types and to make recordings of this music. Many of these recordings were aired on the "Traditional music of Texas" radio program.
Keywords: Folk music : Texas : History and criticism; Folk musicians : Texas : Biography; Folk musicians : Texas : Interviews; Texas : Social life and customs : 20th century; Texas : Social life and customs : 21st century; Texas : Biography